Catalpol Enhances Neurogenesis And Inhibits Apoptosis Of New Neurons Via BDNF, But Not The BDNF/Trkb Pathway - Zhu HF; Shao Y; Qin L; Wang JH; Feng S; Jiang YB; Wan D (Dove Medical Press, 2019)
Hui-Feng Zhu,1,* Yali Shao,1,* Lei Qin,1,* Jing-Huan Wang,1 Shan Feng,1 Yun-Bin Jiang,1 Dong Wan2 1Department of Pharmacy, College of Pharmaceutical Sciences and Chinese Medicine, Southwest University, Chongqing 400715, People’s Republic of China; 2Department of Emergency, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hui-Feng ZhuDepartment of Pharmacy, College of Pharmaceutical Sciences and Chinese Medicine, Southwest University, Chongqing 400715, People’s Republic of ChinaEmail zhfbswu@swu.edu.cnDong WanDepartment of Emergency, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of ChinaTel +86-23-68251225Email wandongcqykdx@126.comBackground: The role of catalpol in brain neurogenesis and newborn neuron survival has not been previously determined in permanent middle cerebral artery occlusion (pMCAO).Methods: Fifty-four rats were divided into 6 groups: pMCAO (model, n=9); sham operation (NS, n=9); catalpol treatment (5 mg/kg and 10 mg/kg subgroups, n=9 each); K252a (n=9); and K252a+catalpol 5 mg/kg (n=9) with stroke. The effects of catalpol on behavior, neurogenesis surrounding the infarction ipsilateral to pMCAO, and the expression of brain-derived neurotrophic factor (BDNF) and its receptor (TrkB) were evaluated. Vehicle or, K252a (i.p.), an inhibitor of TrkB phosphorylase.Results: Repeated administration of catalpol reduced neurological deficits and significantly improved neurogenesis. Catalpol increased the number of newborn immature neurons, as determined by BrdU+-Nestin+ and BrdU+-Tuj-1+ staining, and downregulated cleaved caspase 3 in Tuj-1+ cells at day 7 following stroke. Moreover, catalpol increased the protein expression of Tuj-1, MAP2, and the Bcl-2/Bax ratio, as determined using Western blot. Catalpol also significantly increased brain levels of BDNF, but not TrkB, resulting in enhanced survival of newborn neurons via inhibition of apoptosis.Conclusion: Catalpol may contribute to neurogenesis in infarcted brain regions and help promote the survival of newborn neurons by activating BDNF, but not BDNF/TrkB signaling.Keywords: catalpol, neurogenesis, permanent middle cerebral artery occlusion, pMCAO, brain derived neurotrophic factor, BDNF, neurological function